Bone marrow deficient in IFN-γ signaling selectively reverses GVHD-associated immunosuppression and enhances a tumor-specific GVT effect - Capitini, Christian M. (American Society of Hematology, 2009)
Vaccine-based expansion of T cells is one approach to enhance the graft-versus-tumor effect of allogeneic bone marrow transplantation (BMT), but the complex immunobiology of the allogeneic environment on responses to tumor vaccines has not been well characterized. We hypothesized that subclinical graft-versus-host disease (GVHD) impairs immunity, but modulation of gamma interferon (IFN-γ) signaling could reverse this effect. Dendritic cell vaccines and donor lymphocyte infusions (DLIs) were incorporated into a minor histocompatibility antigen–mismatched, T cell–depleted, allogeneic BMT mouse model. Animals were then challenged with H-Y expressing tumors. CD4(+) and CD8(+) responses to H-Y were diminished in vaccinated allogeneic versus syngeneic BMT recipients with DLI doses below the threshold for clinical GVHD, especially in thymectomized hosts. IFN-γ receptor 1–deficient (IFN-γR1(−/−)) T cells cannot cause GVHD but also have diminished vaccine responses. Remarkably, IFN-γR1(−/−) bone marrow abrogates GVHD, allowing higher DLI doses to be tolerated, but improves vaccine responses and tumor protection. We conclude that tumor vaccines administered after allogeneic BMT can augment graft-versus-tumor if GVHD is avoided and that prevention of IFN-γ signaling on donor bone marrow is an effective approach to preventing GVHD while preserving immunocompetence.